GENERAL CHARACTERISTICS OF THE FEATURES OF CERTAIN TYPES OF ADMINISTRATIVE PROCEEDINGS - Avagyan, Norayr (State and Law, 2022)
In the article "General characteristics of the features of certain types of administrative proceedings", the author duly conducted a comprehensive study of the legal foundations of the features of certain types of administrative proceedings, their boundaries and possible limitations. The article highlights the fundamental qualities that may be suitable for improving domestic legislation according to predictable criteriaIn the article, the author put forward the following reasoned positions:-Features of the proceeding are special rules of administration in certain areas for the effective implementation of the functions of state power.-In certain types of proceedings, individuals are guaranteed by the fundamental provisions of the protection of rights and freedoms provided for by the Constitution and the Law "On the Basics of Administration and Administrative Proceedings”-the legitimate purpose of establishing the features of proceeding is to improve the efficiency of administration and mechanisms for protecting the rights and freedoms of individuals in this area.-when establishing the features of proceeding, it is necessary to observe a reasonable balance between regulations that serve the efficiency of administration and those that protect the rights and freedoms of individuals.-the features of proceeding can be established exclusively by law or international treaties.
Keywords: separate types of administrative proceedings; peculiarities of administrative proceedings; efficiency of administration; special rules of administration